Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1002/qua.22027
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of geometric, electronic, and vibrational properties for all pentagon/hexagon‐bearing isomers of fullerenes C38, C40, and C42

Abstract: ABSTRACT:The self-consistent-charge density-functional tight-binding (SCC-DFTB) method is employed for computing geometric, electronic, and vibrational properties for various topological isomers of small fullerenes. We consider all pentagon/hexagonbearing isomers of C 38 , C 40 , and C 42 as the second part of a larger effort to catalogue the CC distance distributions, valence CCC angle distributions, electronic densities of states (DOSs), vibrational densities of states (VDOSs), and infrared (IR) and Raman sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 23 publications
4
16
0
Order By: Relevance
“…Finally, C 42 was chosen as an intermediate size cluster with a propensity to form fullerenes. For this cluster, 45 nonequivalent fullerene isomers could be identified [68] and the REBO potential predicts that the most stable isomer is the only fullerene with D 3 symmetry, in accordance with DFT calculations [69,70] but at variance with the earlier study by Kosimov et al [9] who found a graphene flake as for C 24 .…”
Section: Reference Structuressupporting
confidence: 84%
“…Finally, C 42 was chosen as an intermediate size cluster with a propensity to form fullerenes. For this cluster, 45 nonequivalent fullerene isomers could be identified [68] and the REBO potential predicts that the most stable isomer is the only fullerene with D 3 symmetry, in accordance with DFT calculations [69,70] but at variance with the earlier study by Kosimov et al [9] who found a graphene flake as for C 24 .…”
Section: Reference Structuressupporting
confidence: 84%
“…An argument in favor of using SCC‐DFTB for the analysis of π ‐conjugated systems is the successful application of this method in studying analogous properties of finite and infinite linear carbon chains 65. A comparison with experimental and more advanced theoretical results demonstrated good performance of the approximate approach, which was successfully used in our group for a number of interesting applications 66–75. Another very important advantage of using the SCC‐DFTB method for our investigation is the possibility of a direct comparison with the analogous solid‐state results.…”
Section: Introductionmentioning
confidence: 72%
“…The resulting finite temperature, dynamic vibrational FT-TCF/DFTB spectra, used previously in a number of studies, [32][33][34][35][36][37][38][39] can be compared with the usual NMA/DFTB spectra, which are readily computable using the analytical SCC-DFTB Hessian code [40][41][42] and have been reported in a number of publications. [43][44][45][46][47] Note that the benchmark calculations suggest that SCC-DFTB is more accurate than other semi-empirical methods for vibrational analysis, 48 especially when used in conjunction with the parameters re-optimized especially for this purpose. 49 In the current study, we employ the FT-TCF/DFTB formalism for modeling the IR spectra of methanol clusters.…”
Section: Introductionmentioning
confidence: 99%